Improving the Quality of Broiler Duck Carcasses with the Addition of Meniran Plan (Phylanthus niruri L.) Extract as a Feed Additive - Lestariningsih Lestariningsih; Fatra Nonggala Putra (Journal of Development Research, 2021)
The purpose of this research was to determine the improvement of the carcass quality of broiler ducks with the addition of meniran extract as a feed additive. This is based on the fluctuating price of feed 70 – 80% is part of the operational costs and the prohibition on the use of antibiotics requires alternative feed additives that are safe for human consumption. This research was carried out in Juni – August 2021 in Dayu Village, Nglegok District Blitar Regency. The method used is experimental with 4 treatments and 3 replications. The design used is Completely Randomized Design. The result showed that giving meniran extract as a feed additive could improve the carcass quality of broiler duck including carcass weight and carcass percentage and dit not have a significant effect on slaughter weight. It is recommended to use meniran plan extract level 3% to improve the carcass quality of broiler ducks.